Proces szacowania kosztu kapitału spółki akcyjnej - Hucik-Gaicka, Sylwia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article discussed the methodology of estimating the cost of capital of stock exchange companies and concluded that no perfect method existed, because each of them had certain drawbacks (economic parameters were unimportant e.g. statistically, unsteady, difficult to establish and to interpret them). The reasons for that are, among others, the lack of the expert knowledge, particularly theoretical one. The more experienced the expert, the more accurate assessment of the cost of capital. Researches of practitioners and theoreticians confirm it. They paid attention to the lack of the access to the credible information necessary to carry out calculations. A thesis of the article was proven in the process that the lack of the credible information about the company in a considerable degree influenced the choice of the method of cost of capital assessment. It requires further theoretical studies particularly numerous empirical researches. It is possible to suppose that the significance of the cost of capital-related issues will grow while the capital market stabilizes. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 96-116